TECTONICS STRESS IN THE EARTH'S CRUST: ADVANCES IN THE WORLD STRESS MAP PROJECT - Sperner B.; Müller B.; Heidbach O.; Reinecker J.; Fuchs K.; Delvaux D. (My University, 2003)
Tectonic stress is one of the fundamental data sets in Earth sciences comparable with topography, gravity, heat flow and others. The importance of stress observations for both academic research (e.g. geodynamics, plate tectonics) and applied sciences (e.g. hydrocarbon production, civil engineering) proves the necessity of a project like the World Stress Map for compiling and making available stress data on a global scale. The World Stress Map project offers not only free access to this global database via the Internet, but also continues in its effort to expand and improve the database, to develop new quality criteria, and to initiate topical research projects. In this paper we present (a) the new release of the World Stress Map, (b) expanded quality ranking schemes for borehole breakouts and geological indicators, (c) new stress indicators (drilling-induced fractures, borehole slotter data) and their quality ranking schemes, and (d) examples for the application of tectonic stress data.